Effect of welding parameters on lap shear force of similar and dissimilar friction stir spot welded aluminium alloys - Ahmed Esmael Mohan; Zainuddin Sajuri; Amir Hossein Baghdadi; Nashrah Hani Jamadon (Fakulti Kejuruteraan ,UKM,Bangi., 2024)
Friction stir spot welding (FSSW) is a solid-state single-point welding technique that uses a rotating tool consisting of a shoulder and a pin for joining nonferrous metals and alloys. FSSW produces a keyhole at the welding point, which decreases the mechanical strength of the joints. This study investigates the influences of tool rotational speed (1000, 1250, and 1500 rpm) and dwell time (5, 10, and 15 s) on the shear fracture load of the FSSW joints. Two different grades of aluminium alloy plates, i.e., AA6061 and AA7075 were used to produce similar (7075-7075 and 6061-6061) and dissimilar (6061-7075) alloy joints. The plates with a thickness of 3 mm were folded above each other before a rotating tool pin was plunged through the thickness of the top plate to obtain an FSSW lap joint. It was found that tool rotational speed and dwell time induced a considerable impact on the microstructure, and shear strength. The results indicated that the grain size of microstructure in similar and dissimilar joints was affected by the rotational speed and dwell time. The grain size of the microstructure increased as rotational speed and dwell time increased. The results also showed that a tool rotational speed of 1250 rpm and dwell time of 10 s gave the highest shear fracture load for 7075-7075 similar and 6061-7075 dissimilar joints. However, for 6061-6061 similar joints, the highest mechanical strength was obtained at 1250 rpm and 10 s.